Nutraceuticals and Their Contribution to Preventing Noncommunicable Diseases - Aurora Garza-Juárez; Esther Pérez-Carrillo; Eder Ubaldo Arredondo-Espinoza; José Francisco Islas; Diego Francisco Benítez-Chao; Erandi Escamilla-García (Foods, 2023)
The high rate of deaths around the world from noncommunicable diseases (NCDs) (70%) is a consequence of a poor diet lacking in nutrients and is linked to lifestyle and environmental conditions that together trigger predisposing factors. NCDs have increased 9.8% of public health spending worldwide, which has been increasing since 2000. Hence, international organizations such as the WHO, the Pan American Health Organization, and the Food and Agriculture Organization of the United Nations have been developing strategic plans to implement government and economic policies to strengthen programs in favor of food security and nutrition. A systematic review is presented to document an analysis of the origin and characteristics of obesity, cardiovascular disease, chronic respiratory diseases, diabetes, and cancers affecting a large part of the world’s population. This review proposes a scientifically based report of functional foods including fruits, vegetables, grains, and plants, and how their bioactive compounds called nutraceuticals—when consumed as part of a diet—benefit in the prevention and treatment of NCDs from an early age. Multifactorial aspects of NCDs, such as culture and eating habits, are limitations to consider from the clinical, nutritional, and biochemical points of view of everyone who suffers from them.